2011
DOI: 10.17221/7/2011-rae
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of biodegradable hydraulic fluid with mineral oil on the basis of selected parameters

Abstract: Majdan R., Kosiba J., Tulík J., Kročková D., Šinský V., 2011. The comparison of biodegradable hydraulic fluid with mineral oil on the basis of selected parameters. Res. Agr. Eng., 57 (Special Issue): S43-S49.The paper presents a comparison of two fluids quality. The first one was mineral oil type UTTO which is commonly used in the transmission and hydraulic systems of agricultural tractors. The second one tested was biodegradable hydraulic fluid type ERTTO which could replace the toxic mineral oil. Both fluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The fl ow characteristics of hydraulic pump were investigated at experimental laboratory equipment so the hydraulic pump was removed from tractor and then mounted on laboratory equipment. There was not found negative impact of the oil MOL Farm UTTO Synt for hydraulic pump operation located in hydraulic circuit of the tractor by fl ow characteristics measurements Tulik et al, 2013;Majdan et al, 2011). Measurements published in this article were executed directly on the tractor in verifying the fl ow characteristics of hydraulic pump but the conclusion is the same as these authors.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The fl ow characteristics of hydraulic pump were investigated at experimental laboratory equipment so the hydraulic pump was removed from tractor and then mounted on laboratory equipment. There was not found negative impact of the oil MOL Farm UTTO Synt for hydraulic pump operation located in hydraulic circuit of the tractor by fl ow characteristics measurements Tulik et al, 2013;Majdan et al, 2011). Measurements published in this article were executed directly on the tractor in verifying the fl ow characteristics of hydraulic pump but the conclusion is the same as these authors.…”
Section: Discussionmentioning
confidence: 59%
“…The fl ow effi ciency of the hydraulic pump was defi ned from measured values and their statistical processing by standardized normal distribution. Calculation of the fl ow effi ciency is based on the relationship (1) (Majdan et al, 2011). …”
Section: Organic Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Tkáč et al (2008) suggested devices for tests of biodegradable hydraulic fluids destined for tractors. Other authors (Majdan et al, 2010, Majdan et al, 2011 described the methods for smart inspection of biodegradable transmission oil of tractor and they provided comparison of biodegradable hydraulic fluid with mineral oil on the basis of selected parameters. Test of biodegradable transmission and hydraulic fluid designed for agricultural tractors and study of ecological fluid properties under operational conditions of tractors were introduced in the works (Tkáč et al, 2012a, Tkáč et al, 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…However, this can be overcome with the use of additives and by modifying the fatty acid composition of the basestock (Kržan et al, 2010;Gustone et al, 2007). Structural limitations of naturally occurring basestocks restrict the application of vegetable oil hydraulic fluids to moderate temperatures (Schneider, 2006;Majdan et al, 2011;Tkáĉ et al, 2010).…”
Section: Introductionmentioning
confidence: 99%